Juridical Analysis in The Formation of Government Regulations in Lieu of Law No. 11 of 2020 Concerning Job Copyright - Nugroho Budi Kisdiyanto; Labib Muttaqin (Proceeding International Conference Restructuring and Transforming Law, 2023)
This study aims to conduct a juridical analysis of the formation process of Government Regulation in Lieu of Law (Perppu) No. 11 of 2020 on Job Creation. The Perppu is a legal instrument adopted by the Indonesian government as an effort to accelerate the implementation of economic policies related to structural reforms. The research method used in this thesis is normative legal research with a statutory approach. The analysis is conducted on the legal basis for the formation of Perppu, including the president's authority in issuing Perppu and its relation to the role of the DPR in the formation of laws. The results of the analysis show that the formation of Perppu No. 11/2020 on Job Creation is based on an emergency and urgency that is considered to require swift action. However, there are debates regarding the president's authority to issue Perppu, especially in terms of time restrictions and the material regulated in the Perppu. This research contributes to understanding the juridical process of Perppu No. 11/2020 on Job Creation, as well as its implications for the legal system and democracy in Indonesia. The findings in this research are expected to be taken into consideration for the government, legislative institutions, and the community in drafting and evaluating regulations related to structural reforms.